Drug-induced long QT syndrome increases the risk of drowning. (February 2016) - Vincenzi, Frank F.
Abstract: There is strong evidence linking inherited long QT syndromes with an increased risk of drowning due to fatal arrhythmias in the water. Drug-induced long QT syndrome (DILQTS) is hypothesized to increase the risk of drowning by similar mechanisms. It is suggested that QT prolongation caused by a drug or drugs, when combined with the autonomic conflict associated with the mammalian dive reflex and/or the cold shock reflex, sets up conditions that may result in a sudden fatal arrhythmia while in water – thus an increased risk of drowning related to a drug-induced prolongation of the QT interval. Many widely used drugs prolong the QT interval thus raising a drug safety issue that needs confirmation or refutation.